Latest Trend of Milk Derived Exosomes: Cargos, Functions, and Applications - Feng, Xin; Chen, Xiaolin; Zheng, Xucan; Zhu, Hui; Qi, Qien; Liu, Shen; Zhang, Huihua; Che, Jianwei (Frontiers in Nutrition, 2021)
Exosomes are nanosized phospholipid bilayer vesicles released to the extracellular environment. Exosomes from various tissues or cells are being studied and there has been a growing interest in milk exosomes research due to their emerging role as messengers between cells and the fact that it can be produced in large quantities with rich source of milk. Milk derived exosomes (MDEs) contain lipids, microRNAs, proteins, mRNAs as well as DNA. Studies of exosome cargo have been conducted widely in many research areas, especially exosomal miRNAs. In this paper, we reviewed the current knowledge in isolation and identification, cargos, functions mainly in intestinal tract and immunity system of MDEs. Its application as drug carriers and diseases biomarker are also discussed. Furthermore, we also consider critical challenges of MDEs application and provide possible directions for future research.